2012
DOI: 10.1016/j.genm.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Effects of 2-Methoxyestradiol on Angiotensin Type 1 Receptor Down-Regulation in Rat Liver Epithelial and Aortic Smooth Muscle Cells

Abstract: Delayed onset of cardiovascular disease among females is not well understood, but could be in part due to the protective effect of estrogen before menopause. Experimental studies have identified the angiotensin type 1 receptor (AT1R) as a key factor in the progression of CVD. In this study, we examined the effects of the estrogen metabolite, 2-methoxyestradiol (2ME2), on AT1R expression. Rat liver cells were exposed to 2ME2 for 24 h and angiotensin II (AngII) binding and AT1R mRNA expressions were assessed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 82 publications
3
17
1
Order By: Relevance
“…33,34 2-ME in a rat liver epithelial cell line (WB cells) and vascular smooth muscle cells downregulated Ang II binding and AT1a receptor mRNA. 35 However, Cyp1b1 gene deletion that minimizes both the basal and Ang II-induced increase in plasma levels of 2-ME did not alter renal AT1a receptor or ACE expression in female mice. 16 In this study, ovarirectomy or infusion of Ang II in OVX mice also did not alter renal mRNA expression of AT1a receptor or ACE .…”
Section: Discussionmentioning
confidence: 91%
“…33,34 2-ME in a rat liver epithelial cell line (WB cells) and vascular smooth muscle cells downregulated Ang II binding and AT1a receptor mRNA. 35 However, Cyp1b1 gene deletion that minimizes both the basal and Ang II-induced increase in plasma levels of 2-ME did not alter renal AT1a receptor or ACE expression in female mice. 16 In this study, ovarirectomy or infusion of Ang II in OVX mice also did not alter renal mRNA expression of AT1a receptor or ACE .…”
Section: Discussionmentioning
confidence: 91%
“…Using the method described previously (Koganti et al, 2012), WB cells were grown in chamber slides (Lab-Tek, Naperville, IL) to 75–80% confluence and exposed to agents separately or in combination as described in the figure legends. Following 1 h incubation at 37°C, cells were washed with ice-cold PBS, fixed with 3% paraformaldehyde in PBS for 30 minutes at 22°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, a binding site or specific mechanism has not been attributed to its effects. Previously, we have shown that 2ME2 specifically down-regulates angiotensin AT 1 receptor gene transcription and protein expression in rat liver epithelial cells and aortic smooth muscle cells (Koganti et al, 2012). Moreover, this effect was not affected by estrogen receptor blocker (Fulvestrant), suggesting that 2ME2’s down-regulatory effect was unrelated to classical estrogen signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen replacement reduced the activity of casein kinase II and thus increased the formation of interactions between Egr-1 and Sp1. Especially with regard to our own research (Koganti et al, 2012) which has seen a down-regulatory effect by estrogen metabolites through extra-nuclear mechanisms, this comes as a link between disparate phenomena connected by ERK1/2. With regard to direct ERK1/2 activation by 13cRA, it may bind a number cytosolic binding proteins, such as CRABP-II or FABP5, leading to divergent effects through distinct signal transduction pathways (Schug et al, 2008) resulting in tissue-specific effects.…”
Section: Discussionmentioning
confidence: 96%
“…Growth factors, such as growth hormone, insulin, platelet-derived growth factor, and epidermal growth factor have a direct up-regulatory effect on AT1R transcription, acting through cis -acting elements (Wyse et al, 2000). Alternatively, AT1R (AT1 A R – in studies of rodent species) transcription may be down-regulated by treatment with tannic acid (Yesudas et al, 2012), the estrogen metabolite 2-methoxyestradiol (Koganti et al, 2012), or high glucose (Thomas & Thekkumkara, 2004), a study in which we isolated a novel glucose response element (GluRE), though characterization of cis -acting elements for the other agents remains undetermined. As this receptor is regulated in multiple ways, addressing the mechanism of gene transcription is essential developing better strategies to control the effects of AngII.…”
Section: Introductionmentioning
confidence: 99%